SIPMAMA ( SISTEM INFORMASI PELAYANAN ADMINISTRASI KELURAHAN ) PADA KANTOR LURAH MAYANG MANGURAI BERBASIS WEB - afrizal, afrizal; Kharsela, Yeni (LP2M Universitas Nurdin Hamzah, 2024)
The sub-district office of Mayang Mangurai has administrative services, namely correspondence, the problem is that they are still using Microsoft Office Word with a copy paste system. In the process of requesting a letter, you need to come to the location directly and sometimes you must go back and forth several times to complete the letter. The purpose of this study is to assist and facilitate the population administration process at the Mayang Mangurai village office. The application is built using Visual Studio Code and XAMPP, using the PHP and MYSQL programming languages. This application produces information about the village activity program, profiles, the latest village news, and online letter writing services that can be accessed by residents in Mayang Mangurai Village. The input needs of this application are Administrators who fully manage Login Data, Admin Data, Population Data and Letter Data, Admin Login Process Needs, Resident Login and Letters, the output of this application is Certificate, Domicile Letter, Business Domicile Letter, Marriage Certificate N1, SITU recommendation letter and Certificate of Heirs.